Assessment of health care providers’ and parents satisfaction about care decisions and care provided to the patients admitted in Pediatric Intensive Care Unit: A descriptive study - Kaur, Amarpreet; Kaur, Harshdeep; Kumari, Nidhi; Kumari, Rja; Rani, Suman; Kalyan, Geetanjli; Muralidharan, Jayshree; Ghai, Sandhya (Indian Journal of Child Health, 2018)
Background: Hospitalisation is a stressful situation especially for children. Health care providers (HCPs) play an important role in caring for the sick children. Objective: To assess the health care providers’ collaboration and satisfaction about care decisions and parents’ satisfaction about care provided to the patients admitted in Pediatric Intensive Care Unit. Materials and Methods: This was a descriptive study conducted among 32 HCPs working in PICU and 50 parents of children admitted to the PICU of a tertiary care teaching and referral hospital in India. The subjects were selected by total enumeration sampling method. Information profile details and data related to parental satisfaction were gathered using a structured interview schedule. Data related to HCPs’ collaboration and satisfaction about care decisions were gathered using a structured questionnaire. The data were analyzed using SPSS (Version 20.0). Results: Majority of the parents were highly satisfied (92%) with the care provided by the HCPs. More than two-third (87.5%) of the HCPs were highly satisfied with the collaboration among them related to care decisions. Conclusion: Majority of the parents of children admitted to PICU, were highly satisfied with the care provided to their children. Furthermore, most HCPs showed a high level of collaboration among themselves and were satisfied with the care decisions related to the PICU children.